2014
DOI: 10.4236/fns.2014.52016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Green Rooibos on Physical Endurance in Swimming Mice

Abstract: Green rooibos made from unfermented rooibos leaves contains high amounts of aspalathin. Dietary green rooibos is expected to increase physical endurance and decrease physical fatigue, because aspalathin has antioxidant activity and stimulates glucose uptake in muscle tissue. The aim of this study was to validate the effects of green rooibos and aspalathin by using a swimming mouse model. Dietary green rooibos and aspalathin tended to increase swimming time in mice. This beneficial effect might be induced by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…This study showed that rooibos extract attenuates the effects of DEP on serum ALT and AST activities, indicating the hepato-protective role of rooibos extract on diesel exhaust particles induced hepatic damage. These findings were in agreement with the reported health promoting effects of rooibos in mice and humans (Watanabe et al, 2014;Marnewick et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…This study showed that rooibos extract attenuates the effects of DEP on serum ALT and AST activities, indicating the hepato-protective role of rooibos extract on diesel exhaust particles induced hepatic damage. These findings were in agreement with the reported health promoting effects of rooibos in mice and humans (Watanabe et al, 2014;Marnewick et al, 2011).…”
Section: Resultssupporting
confidence: 93%